Uma proposta de intervenção ao cuidador principal dos pacientes com doença renal crônica em hemodiálise - Cavalcante, Tarciana Elias (2012)
The present study had the aim to understand repercussions of chronic renal patient s illness and hemodialysis treatment in the lives of main caregivers, with the goal to elaborate and implement a psychological-educational intervention. A qualitative research was conducted using Thematic Content Analysis technique. This study is composed by three papers: one theoretical approach and two empirical ones. In order to carry out the second and third studies, ten relatives of people with chronic renal disease in hemodialysis treatment were recruited. The first paper refers to a literature review on Chronic Renal Failure, with focus on its concept, main causes, characteristics, treatment and the history of hemodialysis. Consulted literature highlights that despite the technological evolution of hemodialysis treatment, which brought up better quality of life to chronic renal patients, it also brought up physical, emotional, social, economic and cultural implications to them and their families. The second paper is on caring and its repercussions in the family, especially regarding the main caregiver. Data analysis of the interviews showed that chronic renal disease and hemodialysis treatment require the family to adapt to a new routine and that caregivers also need caring. In the third paper, the elaboration and implementation of an intervention proposal for this group of relatives is described. Lipp's Inventory of Stress Symptoms in Adults was used to assess the level of stress in caregivers before and after the intervention. The need for relatives of patients in hemodialysis treatment to be assisted in a space that can facilitate the creation, reinvention and/or strengthening of coping mechanisms was observed.